Clinicopathological and molecular aspects of foregut gastrointestinal stromal tumours. Issue 1 (22nd November 2012) - Chen, Jason; Gundara, Justin S.; Haddad, Richard; Schiavone, Vivienne; Meldrum, Cliff; Samra, Jaswinder S.; Gill, Anthony J.; Hugh, Thomas J.
Abstract Background Gastrointestinal stromal tumours (GISTs) are the most common gastrointestinal mesenchymal tumour. This study describes clinicopathological and molecular characteristics in association with clinical outcome, in patients undergoing foregut GIST resection. Methods Clinicopathological data were collated retrospectively for 40 consecutive foregut GISTs. Mutational analysis (quantitative polymerase chain reaction) for KIT exons 9, 11, 13 and 17 and PDGFRa exon 18 was performed on paraffin‐embedded tissue (40 primary tumours and three metastases). Results The median age was 63 years (range: 40–92), and melaena was the most common presentation (30%). Patients undergoing a totally laparoscopic excision had the shortest mean hospital stay (5.5 days). Over a median of 72‐month follow‐up, seven patients developed recurrence/metastases. Tumour size and mitotic rate correlated with recurrence (P < 0.01; <0.01) and mortality (P = 0.03; <0.01). KIT (23/40) or PDGFRa (12/40) mutations were found in 87.5% of the primary tumours. Only patients with KIT mutations suffered mortality (n = 4; P = 0.19) and no patient with a PDGFRa developed recurrence (P = 0.13). Conclusions Tumour site, size and mitotic rate were confirmed as prognostic markers. While KIT and PDGFRa mutations were associated with negative and positive outcomes, respectively, this did not prove to be significant. The clinical impact of these findings may only become apparent in larger series.